Abortion seeking behaviour: a study from tertiary care hospital - R., Uma Maheswari; T. P., Jayanthi (International Journal Of Community Medicine And Public Health, 2017)
Background: With the legislation of the medical termination of pregnancy (MTP) act in 1971, India became one of the first countries legalizing abortion on moderately liberal grounds for women to access safe abortion services. But MTP is often used as the most important method of fertility regulation by the community in the struggle to control family size. Though MTP is a safe procedure and legalised, it is not free from complications and it is dangerous to use it for spacing. Therefore, the present study was undertaken to study the factors influencing MTPs & the subsequent adoption of contraceptive methods following MTP. The objectives of the study were to study the socio- demographic and obstetric profile of women undergoing termination of pregnancy and to study the reasons for termination of pregnancy and the concurrent contraceptive methods adopted by these women Methods: A cross-sectional study was conducted among women who underwent MTP at the hospital during the study period. The details regarding their socio demographic profile, previous obstetric history, reason for seeking abortion and acceptance of post abortal contraception were taken. Results: Among the 184, MTP seekers72.3% of women were below the age of 30, 75% of women resided in urban area and 72.3% of the women were either illiterate or had primary education.95.1% of seeking termination of pregnancy was with gestational age of ≤12 weeks and 94.6% with parity ≤2. Family completed (85.9%) was the main reason for current termination of pregnancy. The concurrent contraceptive adopted were Cu-T and permanent sterilization by 6% and 87.5% women respectively. Conclusions: Eligible couples have to be educated regarding the availability of different methods of contraceptives and their proper use to avoid pregnancy as long as they want.